IDENTIFYING THE FACTORS EFFECTING THE PERSONAL CONCERNS OF CONSUMERS IN ACCEPTING NEW PRODUCTS: A CASE STUDY ON THE COSMETIC PRODUCTS OF PAYOON TRADING COMPANY - Ramezani, Yousef; Alizadeh, Negar; Hashemiamin, Arezoosdat (International Journal of Supply Chain Management, 2019)
The success of new products is accounted as the superior factor for the accomplishment of companies. The several investigations show that the rate of the failure of new products development has been mentioned as a basic problem in many of companies. One of the reasons of this failure is the high level of concern of the consumers in accepting the new product. The purpose of this research is identifying the effect of these concerns on accepting the new products. This research is practical in terms of purpose and is exploratory survey in terms of methodology. The tool of gathering the information in the stage of identifying the components of personal concerns of consumers is interview and in the stage of testing the hypothesis of research is questionnaire. The population of this research includes consumers of cosmetic product of Payoon trading company. The sample of interview is 23 people and the model of questionnaire is determined by simple random sampling and the formula of determining the volume of Cochran sample is calculated 246 people (the consumers of the products and the expertise). For testing the hypotheses the t-test is used and for ranking these factors the Friedman rating test is used. The results of research show that the fame and reputation has no significant effect on personal concern of users in accepting the new products. Therefore, it has the lowest priority in Friedman rating test. But the other variables including credit, price, product recognition, standards, and ease of use, reliance, and easy accessibility to product have significant effect on personal concerns of consumers in accepting the new product which are mentioned based on the priority of Friedman test.